Articulating Hindu masculinity and feminity: "Shuddhi" and "Sangathan" movements in united provinces in the 1920s - Gupta, Charu (Economic & political weekly, 1998)
The history of gender is about both women and men. According to the author, gender is a social construction and definitions of masculinity and feminity are social forces. She examines the interrelationship between masculinity and feminity and Hindu communal militant organisations in early 20th century United Provinces (now Uttar Pradesh) in the specific context of the 'sangathan' and 'shuddhi' movements. (DÜI-Sen)